Manajemen Pengolahan Sumber Daya Manusia Dalam Meningkatkan Kualitas Pendidikan di SDN Lancong Kecamatan Sungai Mas Kabupaten Aceh Barat - munawarah munawarah; Sri Wahyu Handayani (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2023)
Education is something that absolutely must be met by students as a form of learning experience, either directly or indirectly, to become the basis for changing behavior towards maturity. School strategies are important policies of schools to achieve the goal of improving and developing the quality of teachers. To improve the role and function of the teacher, it is something that really needs to be considered in teaching management both from the planning, organizing, actuating or motivational aspects of the teacher. Based on observations made at SDN Lancong, the process that occurs in the subjects that are followed by all students, students are less interested in the learning provided by the teacher, based on the results of these observations, research is carried out on Human Resource Processing Management in Improving Education at SDN Lancong . The approach taken in this research is qualitative with descriptive research type. Based on the research that has been done, the results show that in improving the quality of education at SDN Lancong, good management of human resources is needed, as well as increasing the integration of human resource management in improving the quality of education, especially at SDN Lancong, where geographically the location of SDN Lancong is in the interior and its location which is relatively far from the home of the students who mostly access the school on foot. Therefore we need a good management so that the quality of education can increase. Based on the results of the research that has been done, it can be concluded that human resource management is very necessary in an effort to improve the quality and quality of education at SDN Lancong, Sungai Mas District, Aceh Barat Regency, where the current condition is that the number of teachers is still lacking to be able to carry out effective education, so it will affect the learning process and the results to be achieved.